Electrocatalytic materials and electrodes comprising the same, methods of making the same, applications
Patent Information
- Application Number
- CN202510452922.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-10
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]但是,相关技术中,电催化材料的稳定性较差,影响碱性电解槽的可靠性;此外,催化材料通常采用水热反应制备,对于反应容器的密封性要求较高,工业化放大难度高,制备效率低
[0009]根据本申请的实施例,通过在基材表面形成第一表面层和第二表面层,使电催化材料可以兼具较高的活性和稳定性。其中,第一表面层包括含钼、钒中的至少一种元素和镍元素的复合物,第二表面层为包括金属镍的多孔结构,第一表面层中的钼元素和/或钒元素可以在电解过程中缓慢溶出,扩散到第二表面层的多孔结构的孔洞中,以改善电化学反应的化学环境,使电催化材料在长期电解水过程中保持活性;通过第一表面层和第二表面层的双层结构,使电催化材料具有较高的催化活性;由于电催化材料中包括的金属元素种类较少,金属元素之间的相互影响较小,提高了电催化材料的稳定性;此外,第二表面层还可以作为第一表面层的保护层,进一步提高电催化材料的稳定性。
Smart Images

Figure CN122979934A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of catalytic materials technology, specifically to an electrocatalytic material and an electrode therein, its preparation method, and its application. Background Technology
[0002] Alkaline electrolyzers decompose water through electrochemical reactions to produce hydrogen and oxygen. Electrocatalysts, by lowering the activation energy and accelerating charge transfer, enable highly efficient water electrolysis and are crucial materials driving these electrochemical reactions.
[0003] However, in related technologies, the stability of electrocatalytic materials is poor, which affects the reliability of alkaline electrolyzers. In addition, catalytic materials are usually prepared by hydrothermal reaction, which requires high sealing of the reaction vessel, making industrial scale-up difficult and resulting in low preparation efficiency. Summary of the Invention
[0004] In view of this, in order to at least partially solve the aforementioned technical problems, this application provides an electrocatalytic material and an electrode including the same, a method for preparing the same, and applications.
[0005] According to an embodiment of the first aspect of this application, an electrocatalytic material is provided, the electrocatalytic material comprising a first surface layer and a second surface layer sequentially disposed on the surface of a substrate, wherein the first surface layer comprises a composite containing at least one element selected from molybdenum and vanadium and an element nickel, the second surface layer comprises metallic nickel, and the second surface layer has a porous structure.
[0006] According to an embodiment of the second aspect of this application, a method for preparing an electrocatalytic material is provided, comprising: preparing a first initial surface layer on a substrate surface to obtain a first initial surface layer located on the substrate surface; electrodepositing a composite film on the surface of the first initial surface layer away from the substrate, and converting the first initial surface layer into a first surface layer to obtain a first surface layer and a composite film located on the substrate surface, wherein the composite film comprises metallic nickel and an amphoteric metal, and the first surface layer comprises a composite containing at least one element selected from molybdenum and vanadium and an element nickel; removing the amphoteric metal from the composite film by alkaline washing, thereby converting the composite film into the second surface layer to obtain the electrocatalytic material.
[0007] According to an embodiment of the third aspect of this application, an electrode is provided, comprising a substrate and an electrocatalytic material located on the surface of the substrate, wherein the electrocatalytic material on the surface of the substrate is any of the electrocatalytic materials described above.
[0008] According to an embodiment of the fourth aspect of this application, an application of the electrocatalytic material as described above in alkaline water electrolysis for hydrogen production and alkaline water electrolysis for oxygen production is provided.
[0009] According to embodiments of this application, by forming a first surface layer and a second surface layer on the surface of a substrate, the electrocatalytic material can possess both high activity and stability. The first surface layer comprises a composite containing at least one element selected from molybdenum and vanadium, and nickel. The second surface layer is a porous structure containing metallic nickel. The molybdenum and / or vanadium elements in the first surface layer can slowly dissolve during electrolysis and diffuse into the pores of the porous structure of the second surface layer, thereby improving the chemical environment of the electrochemical reaction and maintaining the activity of the electrocatalytic material during long-term water electrolysis. The bilayer structure of the first and second surface layers enables the electrocatalytic material to exhibit high catalytic activity. Because the electrocatalytic material contains fewer types of metal elements, the interaction between the metal elements is smaller, improving the stability of the electrocatalytic material. Furthermore, the second surface layer can also serve as a protective layer for the first surface layer, further enhancing the stability of the electrocatalytic material. Attached Figure Description
[0010] The above and other objects, features and advantages of this application will become clearer from the following description of embodiments with reference to the accompanying drawings, in which:
[0011] Figure 1 This is a schematic diagram of the structure of the electrocatalytic material according to an embodiment of this application;
[0012] Figure 2 This is a schematic diagram of the structure of an electrocatalytic material according to another embodiment of this application;
[0013] Figure 3 A partial observation diagram of the radial cross-section of the electrocatalytic material provided in the embodiments of this application;
[0014] Figure 4 The image shows the elemental analysis results of the local energy dispersive X-ray spectroscopy of the cross section of the electrocatalytic material provided in the embodiments of this application;
[0015] Figure 5 X-ray diffraction pattern of the electrocatalytic material provided in the embodiments of this application;
[0016] Figure 6 X-ray photoelectron spectrum of nickel in the electrocatalytic material provided in the embodiments of this application;
[0017] Figure 7 This is a schematic flowchart of the preparation method of the electrocatalytic material according to an embodiment of this application;
[0018] Figure 8 The figure shows the long-term test results of the electrocatalytic materials in the embodiments and comparative examples of this application in an atmospheric pressure electrolyzer.
[0019] [Explanation of Labels in the Attached Image]
[0020] 1-Substrate;
[0021] 2-First surface layer;
[0022] 3-Second surface layer. Detailed Implementation
[0023] The embodiments of this application will now be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of this application. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of this application for ease of explanation. However, it will be apparent that one or more embodiments may be implemented without these specific details. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of this application.
[0024] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.
[0025] When using expressions such as "at least one of A, B, and C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, and C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). When using expressions such as "at least one of A, B, or C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, or C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).
[0026] In realizing the concept of this application, it was discovered that by forming a special bilayer structure on the surface of the substrate, the electrocatalytic material can have both high activity and stability, even with a small number of metal elements.
[0027] Specifically, according to one embodiment of this application, an electrocatalytic material is provided. Figure 1 This is a schematic diagram of the structure of the electrocatalytic material according to an embodiment of this application. Figure 2 This is a schematic diagram of the structure of an electrocatalytic material according to another embodiment of this application, as shown below. Figure 1 and Figure 2As shown, the electrocatalytic material includes a first surface layer 2 and a second surface layer 3 sequentially disposed on the surface of a substrate 1. The first surface layer 2 includes a composite containing at least one element selected from molybdenum and vanadium and an element nickel. The second surface layer 3 includes metallic nickel and has a porous structure.
[0028] According to embodiments of this application, by forming a first surface layer 2 and a second surface layer 3 on the surface of a substrate 1, the electrocatalytic material can possess both high activity and stability. The first surface layer 2 comprises a composite containing at least one element selected from molybdenum and vanadium, and nickel. The second surface layer 3 is a porous structure containing metallic nickel. Vanadium and / or molybdenum in the first surface layer 2 can slowly dissolve during electrolysis and diffuse into the pores of the porous structure of the second surface layer 3, thereby improving the chemical environment of the electrochemical reaction and maintaining the activity of the electrocatalytic material during long-term water electrolysis. The bilayer structure of the first surface layer 2 and the second surface layer 3 enables the electrocatalytic material to exhibit high catalytic activity. Because the electrocatalytic material contains fewer types of metal elements, the interaction between the metal elements is smaller, improving the stability of the electrocatalytic material. Furthermore, the second surface layer 3 can also serve as a protective layer for the first surface layer 2, further enhancing the stability of the electrocatalytic material.
[0029] It is understood that, since vanadium and / or molybdenum in the first surface layer 2 can slowly dissolve and diffuse into the pores of the porous structure of the second surface layer 3 during electrolysis, the second surface layer 3 may also include vanadium and / or molybdenum.
[0030] It should be noted that, considering the availability of raw materials and the ability of vanadium and / or nickel in the first surface layer to dissolve slowly during electrolysis, the valence state of vanadium in the first surface layer 2 can be +4 or +5, preferably +5; the valence state of molybdenum in the first surface layer 2 can be +5 or +6, preferably +6; and the valence state of nickel in the first surface layer 2 can be +2 or +3, preferably +2.
[0031] It should be noted that the first surface layer 2 may be located on at least a portion of the surface of the substrate 1, that is, the first surface layer 2 may be located on all or part of the surface of the substrate 1. The second surface layer 3 may be located on at least a portion of the surface of the first surface layer 2 away from the substrate 1, that is, the second surface layer 3 may be located on all or part of the surface of the first surface layer 2 away from the substrate 1.
[0032] It should be noted that this application does not limit the method for determining the metal elements in the first surface layer 2 and the second surface layer 3. Those skilled in the art can select an appropriate method based on the actual situation. For example, X-ray photoelectron spectroscopy, energy-dispersive X-ray spectroscopy, inductively coupled plasma atomic emission spectrometry, secondary ion mass spectrometry, X-ray diffraction, etc., can be used to determine the complex containing at least one element from molybdenum and vanadium and nickel in the first surface layer 2, and the inclusion of metallic nickel in the second surface layer 3.
[0033] It should be noted that this application does not limit the detection method for the porous structure of the second surface layer 3, and those skilled in the art can select an appropriate detection method according to the actual situation. For example, the porous structure of the second surface layer 3 can be directly observed by means of transmission electron microscopy, scanning electron microscopy, atomic force microscopy, three-dimensional ultra-depth-of-field digital microscopy, etc.
[0034] In some embodiments of this application, the substrate 1 may be a conductive substrate. Conductive substrates are advantageous for preparing electrocatalytic materials via electrodeposition. Furthermore, conductive substrates are also suitable for the application of electrocatalytic materials in electrodes. Optionally, the substrate 1 may include at least one of a metal mesh or a metal foam.
[0035] The metal mesh can be a mesh structure made of metal material through weaving, welding, stamping, or other processes, and can include woven mesh, stamped mesh, welded mesh, etc. For example, the substrate 1 can be a network structure made of metal wires through a weaving process; that is, the substrate 1 can be a metal mesh. In this case, such as... Figure 1 As shown, the first surface layer 2 can be wrapped around the surface of the metal wire, and the second surface layer 3 can be wrapped around the surface of the first surface layer 2 away from the metal wire.
[0036] Metal foam can be a three-dimensional porous metal material. For example, substrate 1 can be a metal foam, such as... Figure 2 As shown, the first surface layer 2 can be located on the surface of the metal foam, and the second surface layer 3 can be located on the surface of the first surface layer 2 away from the metal foam.
[0037] In some embodiments of this application, the material of the substrate 1 may include at least one of nickel and nickel alloys. The nickel alloy may include nickel-chromium alloys, etc. Exemplarily, the substrate 1 may include nickel metal mesh, nickel metal foam, nickel-chromium metal mesh, nickel-chromium metal foam, etc.
[0038] In some embodiments of this application, the substrate 1 can be a surface-treated substrate 1. Surface treatment can include at least one of sandblasting, grinding, chemical etching, and electrochemical etching. Sandblasting can be a surface treatment method that uses a high-pressure airflow to propel abrasive particles such as quartz sand or steel shot at high speed onto the surface of the substrate 1, using mechanical impact to remove oxide layers, burrs, oil stains, or form rough textures. Grinding can be a surface treatment method that uses mechanical tools such as sandpaper, grinding wheels, or grinding stones to physically rub the surface of the substrate 1, forming a rough structure on the surface of the substrate 1. Chemical etching can be a surface treatment method that immerses the substrate 1 in an acid or alkaline solution, dissolving the surface material of the substrate 1 through a selective corrosion reaction to form patterns, grooves, or rough structures. Electrochemical etching can be a treatment method that uses an external electric field to controllably dissolve the substrate 1 in an electrolyte. The above surface treatments can increase the surface area and roughness of the substrate 1, improving the interfacial performance between the substrate 1 and the first surface layer 2.
[0039] It should be noted that, in order to further increase the surface area and roughness of the substrate 1, multiple surface treatment methods can be used in combination. For example, the substrate 1 can be sandblasted and polished in sequence, or polished and chemically etched in sequence, or sandblasted and electrochemically etched in sequence. Relevant technicians can select appropriate surface treatment methods according to actual needs.
[0040] The following is for reference. Figures 3-6 In conjunction with specific embodiments, Figure 1 The electrocatalytic materials shown will be further explained.
[0041] According to embodiments of this application, the first surface layer 2 may have a porous structure. This porous structure can be a three-dimensional network structure composed of interconnected or independent pores. The porous structure of the first surface layer 2 allows for rapid electrolyte penetration and efficient detachment from bubbles, reducing concentration polarization during hydrogen evolution and / or oxygen evolution processes. Furthermore, the porous structure can provide a high density of active sites, accelerating water splitting reactions under alkaline conditions. Figure 3 This is a partial observation diagram of the radial cross-section of the electrocatalytic material provided in an embodiment of this application. Figure 3 It can be seen that the first surface layer 2 has a porous structure, and the second surface layer 3 also has a porous structure.
[0042] It should be noted that this application does not limit the detection method for the porous structure of the first surface layer 2, and those skilled in the art can select an appropriate detection method according to the actual situation. For example, the porous structure of the first surface layer 2 can be directly observed by means of transmission electron microscopy, scanning electron microscopy, atomic force microscopy, three-dimensional ultra-depth-of-field digital microscopy, etc.
[0043] According to embodiments of this application, in the first surface layer 2, the composite containing at least one element selected from molybdenum and vanadium, and nickel, may include at least one element selected from molybdenum and vanadium, and nickel. Optionally, the composite containing at least one element selected from molybdenum and vanadium, and nickel, may include a vanadium-containing compound, a molybdenum-containing compound, a nickel-containing compound, a compound containing both vanadium and nickel, a compound containing both molybdenum and nickel, or at least one of a compound containing both vanadium, molybdenum, and nickel. Exemplarily, the composite containing at least one element selected from molybdenum and vanadium, and nickel, may include at least one of vanadium oxide, vanadium hydroxide, molybdenum oxide, molybdenum hydroxide, nickel oxide, and nickel hydroxide. The composite containing at least one element selected from molybdenum and vanadium, and nickel, can synergistically optimize charge transport at the interface, thereby improving the efficiency of water electrolysis.
[0044] In some embodiments of this application, a complex containing at least one element selected from molybdenum and vanadium, and nickel, may include a complex containing vanadium and nickel. Alternatively, a complex containing vanadium and nickel may include at least one of a vanadium-containing compound, a nickel-containing compound, or a compound containing both vanadium and nickel. Exemplarily, a complex containing vanadium and nickel may include at least one of vanadium oxide, vanadium hydroxide, nickel oxide, and nickel hydroxide. A complex containing vanadium and nickel may include vanadium oxide, vanadium hydroxide, nickel oxide, and nickel hydroxide.
[0045] In some embodiments of this application, the complex containing at least one element selected from molybdenum and vanadium and nickel may further include at least one of metallic vanadium, metallic molybdenum, and metallic nickel.
[0046] In some embodiments of this application, the second surface layer 3 may further include an amphoteric metal, the mass content of which may be less than or equal to 5%. Exemplarily, the mass content of the amphoteric metal may be within any two values of 5%, 4%, 3%, 2%, 1%, 0, or higher. By controlling the mass content of the amphoteric metal to below 5%, a superior catalytic effect of the electrocatalytic material is ensured. Optionally, the amphoteric metal may include at least one of zinc, chromium, and aluminum. Figure 4 This image shows the elemental analysis results of a cross-section of the electrocatalytic material provided in this embodiment of the application. The substrate 1 is a nickel metal mesh. Figure 4 It can be seen that in this local area, the main metal element contained in the substrate 1 and the electrocatalytic material is nickel, with an atomic ratio of up to 95.3%; vanadium is mainly located in the first surface layer 2, with an atomic ratio of 3.9%; and zinc is mainly located in the second surface layer 3, with an atomic ratio of 0.8%.
[0047] In some embodiments of this application, the metallic nickel in the second surface layer 3 is exposed to the environment and can be oxidized by air, adsorb water vapor, etc., to form nickel oxides and nickel hydroxides naturally. That is, the second surface layer 3 may also contain at least one of nickel oxides and nickel hydroxides.
[0048] Figure 5 X-ray diffraction pattern of the electrocatalytic material provided in the embodiments of this application. Figure 5 It can be seen that the three main diffraction peaks can all be attributed to characteristic peaks of nickel. It can be understood that the nickel oxide and nickel hydroxide formed on the surface of the electrocatalytic material are only nanometer thick, and their relative content is small compared to the elemental nickel in the inner layer, so they were not detected by X-ray diffraction.
[0049] Figure 6 The image shows the X-ray photoelectron spectrum of nickel in the electrocatalytic material provided in Example 1 of this application. Figure 6 It can be seen that metallic nickel in the material has three binding energies: 852, 853, and 855 eV, which correspond to Ni, respectively. 0 The materials consist of NiO and Ni(OH)₂. Since XPS can only detect metallic nickel at depths below 10 nm, while the coating thickness can exceed 15 μm, the outer layer of elemental nickel is the primary component of this material. It is understandable that different elements will have different positions in the XPS spectrum; vanadium and zinc mainly appear in the ranges of 500–520 eV and 1015–1025 eV, respectively. The above X-ray photoelectron spectroscopy (XPS) spectra of nickel only focus on nickel in the nickel grid-IV; trace element analysis was not performed.
[0050] According to embodiments of this application, the mass content of nickel in the electrocatalytic material can be 90% to 98%. Exemplarily, the mass content of nickel in the electrocatalytic material can be within any two values between 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or higher. The mass content of vanadium and / or molybdenum in the electrocatalytic material can be 2% to 10%. Exemplarily, the mass content of vanadium and / or molybdenum in the electrocatalytic material can be within any two values between 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or higher.
[0051] It should be noted that the electrocatalytic material can be peeled off from the surface of the substrate 1 by means of ultrasound, then dissolved, and inductively coupled plasma (ICP) test is performed to obtain the content of nickel, vanadium, molybdenum, etc. in the electrocatalytic material. The mass content of nickel can be 90~98%, and the mass content of vanadium and / or molybdenum can be 2~10%.
[0052] According to embodiments of this application, the thickness of the first surface layer 2 can be 15-30 micrometers. Exemplarily, the thickness of the first surface layer 2 can be within the range of any two values above 15 micrometers, 16 micrometers, 17 micrometers, 18 micrometers, 19 micrometers, 20 micrometers, 21 micrometers, 22 micrometers, 23 micrometers, 24 micrometers, 25 micrometers, 26 micrometers, 27 micrometers, 28 micrometers, 29 micrometers, 30 micrometers, or more. The thickness of the second surface layer 3 can be 5-50 micrometers. Exemplarily, the thickness of the second surface layer 3 can be within the range of any two values above 5 micrometers, 10 micrometers, 12 micrometers, 14 micrometers, 16 micrometers, 18 micrometers, 20 micrometers, 22 micrometers, 24 micrometers, 26 micrometers, 28 micrometers, 30 micrometers, 32 micrometers, 34 micrometers, 36 micrometers, 38 micrometers, 40 micrometers, 42 micrometers, 44 micrometers, 46 micrometers, 48 micrometers, 50 micrometers, or more. The thicknesses of the first surface layer 2 and the second surface layer 3 are within the aforementioned range, which can balance the number of active sites and charge transport efficiency of the electrocatalytic material, while enhancing structural stability through interface synergistic optimization.
[0053] According to another embodiment of this application, a method for preparing an electrocatalytic material is provided, such as... Figure 7 As shown, it may include steps S1 to S3.
[0054] In step S1, a first initial surface layer is prepared on the surface of the substrate to obtain the first initial surface layer located on the surface of the substrate.
[0055] In step S2, a composite film is electrodeposited on the surface of the first initial surface layer away from the substrate, and the first initial surface layer is transformed into a first surface layer, resulting in a first surface layer and a composite film located on the substrate surface. The composite film includes metallic nickel and an amphoteric metal, and the first surface layer includes a composite containing at least one element selected from molybdenum and vanadium and an element nickel.
[0056] In step S3, the amphoteric metal in the composite film is removed by alkaline washing, so that the composite film is transformed into a second surface layer, and an electrocatalytic material is obtained.
[0057] According to embodiments of this application, a composite film comprising metallic nickel and a zwitterionic metal is electrodeposited on the surface of a first initial surface layer away from the substrate, and the first initial surface layer is transformed into a first surface layer comprising a composite containing at least one element selected from molybdenum and vanadium and nickel. This yields a first surface layer and a composite film located on the substrate surface. The electrodeposition process is a chemical reaction process, resulting in good interfacial properties between the first surface layer and the composite film. Then, alkaline washing removes the zwitterionic metal from the composite film, transforming it into a second surface layer with a porous structure, thus obtaining an electrocatalytic material. This application makes the preparation process of the electrocatalytic material more controllable through electrodeposition and alkaline washing.
[0058] According to embodiments of this application, a complex containing at least one element selected from molybdenum and vanadium, and nickel, may include a complex containing vanadium and nickel. This complex can synergistically optimize charge transport through interface interaction, thereby improving water electrolysis efficiency.
[0059] According to an embodiment of this application, in step S1, a first initial surface layer is prepared on the surface of the substrate to obtain the first initial surface layer located on the surface of the substrate, which may include steps S11 and S12.
[0060] In step S11, the substrate can be impregnated in an impregnation solution to obtain an impregnated substrate. The impregnation solution includes nickel salt, molybdate and / or metavanadate, and a precipitant.
[0061] In step S12, the impregnated substrate can be calcined under a protective atmosphere to obtain a first initial surface layer on the surface of the substrate.
[0062] According to embodiments of this application, a first initial surface layer is prepared by impregnation and calcination. A chemical reaction process allows elements to permeate each other, enhancing the adhesion between the first initial surface layer and the substrate. Furthermore, the preparation process is gentler and more controllable, resulting in a first initial surface layer with relatively uniform quality. The precipitant can regulate the hydrolysis process during impregnation to achieve homogeneous precipitation.
[0063] In some embodiments of this application, the protective atmosphere can be an inert atmosphere. The protective atmosphere is mainly used to isolate substances such as oxygen and water vapor, preventing material oxidation and corrosion. Those skilled in the art can select a suitable inert atmosphere based on the actual situation. For example, the inert atmosphere may include at least one of helium, neon, argon, krypton, xenon, and nitrogen.
[0064] In some embodiments of this application, the impregnation solution may include nickel salts, molybdates, and precipitants. The impregnation solution may also include nickel salts, metavanadates, and precipitants.
[0065] In some embodiments of this application, in step S11, the nickel salt may include at least one of nickel acetate and nickel nitrate. The metavanadate may include at least one of sodium metavanadate and ammonium metavanadate. The molybdate may include at least one of sodium molybdate and ammonium molybdate. The precipitant may include at least one of urea and melamine. Compared to directly adding a strong alkali, the above precipitants hydrolyze slowly, avoiding excessively high local pH, thereby obtaining a precipitate with uniform particles and high purity.
[0066] In some embodiments of this application, in step S11, the molar ratio of nickel salt, molybdate and / or metavanadate, and precipitant in the impregnation solution can be (1~5):(1~5):(1~50). For example, the molar ratio of nickel salt, molybdate and / or metavanadate, and precipitant can be 1:1:1, 1:1:5, 1:2:10, 1:1:20, 1:1:30, 1:1:40, 1:1:50, 1:2:1, 1:3:1, 1:3:5, 1:3:10, 1:3:30, 1:3:50, 1:4:1, 1:5:1, 1:5:5, 1:5:10, 1:5:30, 1:5:50, 3:1:1, 3:3:1, 3:3:10, 3:3:50, 3:5:1, 3:5:20, 3:5:50, 5:1:1, 5:3:1, 5:5:1, 5:1:30, 5:3:50, or any two of the above ratios. In the impregnation solution, the molar ratio of nickel salt, molybdate and / or metavanadate, and precipitant is within the above range, which can keep the nickel, vanadium and / or molybdenum elements in the first surface layer within a reasonable range, thereby further improving the efficiency of water electrolysis.
[0067] According to an embodiment of this application, step S11, impregnating the substrate in an impregnation solution includes immersing the substrate in an impregnation solution at a temperature of 70-100°C for 1-10 minutes. Exemplarily, the temperature of the impregnation solution can be any two values between 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or higher. The immersion time of the substrate in the impregnation solution can be any two values between 1 minute, 3 minutes, 5 minutes, 7 minutes, 9 minutes, 10 minutes, or higher. The above impregnation process can accelerate ion diffusion and co-precipitation, forming a uniform and dense precursor coating on the substrate surface. Unlike traditional hydrothermal reactions, the impregnation process in this application does not require a sealed, high-pressure reaction environment.
[0068] According to an embodiment of this application, in step S12, the calcination temperature is 500~1000℃. Exemplarily, the calcination temperature can be any two values between 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, or more. The calcination time can be 1~5 hours. Exemplarily, the calcination time can be any two values between 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, or more. Through the above calcination treatment, the precursor coating can be decomposed to form a relatively stable first initial surface layer.
[0069] In some embodiments of this application, in step S2, the electrodeposition solution used for electrodeposition may include a nickel salt, an amphoteric metal salt, and a pH buffer. The nickel salt in the electrodeposition solution includes at least one of nickel sulfate, nickel acetate, and nickel nitrate; the amphoteric metal salt includes at least one of zinc sulfate, zinc acetate, zinc nitrate, chromium sulfate, chromium nitrate, aluminum nitrate, and aluminum sulfate; and the pH buffer includes at least one of boric acid, sodium borate, and phosphoric acid.
[0070] In some embodiments of this application, in step S2, the concentration of the nickel salt in the electrodeposition solution is 0.05~0.2 mol / L. Exemplarily, the concentration of the nickel salt can be 0.05 mol / L, 0.06 mol / L, 0.08 mol / L, 0.10 mol / L, 0.12 mol / L, 0.15 mol / L, 0.17 mol / L, 0.19 mol / L, 0.20 mol / L, or any two of the above values. The concentration of the amphoteric metal salt is 0.01~0.05 mol / L. Exemplarily, the concentration of the amphoteric metal salt can be 0.01 mol / L, 0.015 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.035 mol / L, 0.04 mol / L, 0.045 mol / L, 0.05 mol / L, or any two of the above values. The concentration of the pH buffer is 15-20 g / L. For example, the concentration can be 15 g / L, 15.5 g / L, 16 g / L, 16.5 g / L, 17 g / L, 17.5 g / L, 18 g / L, 18.5 g / L, 19 g / L, 19.5 g / L, 20 g / L, or any two of these values. Within the above range, the concentrations of nickel salt, amphoteric metal salt, and pH buffer in the electrodeposition solution can balance the electrodeposition rate, the quality of the composite film, and the stability of the electrodeposition solution. If the concentration is too high, the electrodeposition quality decreases, and the stability of the electrodeposition solution decreases; if the concentration is too low, the electrodeposition rate is slow.
[0071] According to an embodiment of this application, in step S2, electrodeposition may include: placing a first initial surface layer located on the substrate surface in an electrodeposition solution and repeating the following pulses 200 to 2000 times: current -5 to -20 mA, time 5 to 30 s, current 0 mA, time 5 to 15 s. Exemplarily, in electrodeposition, the number of repeated pulses can be within any two values of 200, 300, 500, 700, 900, 1000, 1200, 1500, 1800, 2000, or more. In the aforementioned pulses, the current can be any two values between -5mA, -8mA, -10mA, -12mA, -15mA, -18mA, -20mA, or higher, and the time can be any two values between 5s, 8s, 10s, 12s, 15s, 18s, 20s, 22s, 25s, 28s, 30s, or higher. When the current is 0mA, the time can be any two values between 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, or higher. Under these pulse conditions, dynamic control of the time dimension can further improve the quality of the composite thin film.
[0072] In some embodiments of this application, in step S2, the amphoteric metal may include at least one of zinc, chromium, and aluminum.
[0073] According to embodiments of this application, in step S3, the amphoteric metal in the composite film can be completely or partially removed by alkaline washing. In some embodiments, the amphoteric metal in the composite film can be completely removed by alkaline washing, in which case the prepared electrocatalytic material does not contain the amphoteric metal. In some embodiments, the amphoteric metal in the composite film can be partially removed by alkaline washing, in which case the prepared electrocatalytic material includes the amphoteric metal. Removing the amphoteric metal in the composite film by alkaline washing can give the prepared second surface layer a porous structure.
[0074] In some embodiments of this application, step S3, alkaline washing may include: immersing the first surface layer and the composite film located on the surface of the substrate in an alkaline solution, and then drying them to obtain the electrocatalytic material.
[0075] In some embodiments of this application, in step S3, the pH of the alkaline solution can be 10-15. Exemplarily, the pH of the alkaline solution can be 10, 11, 12, 13, 13.5, 14, 14.5, 15, or any two of these values. The alkaline solution may include at least one of sodium hydroxide and potassium hydroxide.
[0076] In some embodiments of this application, in step S3, the soaking time can be 4 to 8 hours. Exemplarily, the soaking time can be any two of the following values: 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, or more. Controlling the alkaline washing process is beneficial for better removal of the amphoteric metals, thereby forming a porous structure in the second surface layer.
[0077] According to another aspect of this application, an electrode is provided, comprising a substrate and an electrocatalytic material located on the surface of the substrate, wherein the electrocatalytic material is any of the electrocatalytic materials described above.
[0078] In some embodiments of this application, the electrocatalytic material may include a first surface layer and a second surface layer sequentially disposed on the surface of a substrate, wherein the first surface layer includes a composite containing at least one element selected from molybdenum and vanadium and an element of nickel, the second surface layer includes metallic nickel, and the second surface layer has a porous structure.
[0079] According to embodiments of this application, by introducing electrocatalytic materials onto the electrode surface, the reaction overpotential can be reduced, thereby improving the efficiency and stability of electrolytic catalysis.
[0080] According to another aspect of this application, an alkaline electrolyzer is provided, which may include a cathode and an anode. At least one of the cathode and anode includes a substrate and an electrocatalytic material located on the surface of the substrate. The electrocatalytic material is any of the electrocatalytic materials described above. Exemplarily, the cathode may include a substrate and an electrocatalytic material located on the surface of the substrate, and the anode may include a substrate and an electrocatalytic material located on the surface of the substrate. The anode and cathode may each independently include a substrate and an electrocatalytic material located on the surface of the substrate.
[0081] Alkaline electrolyzers may also include an electrolyte, which can be an alkaline aqueous solution. Technical personnel can select a suitable diaphragm based on actual needs. For example, the electrolyte can be an aqueous solution of potassium hydroxide and / or sodium hydroxide. Further, the electrolyte can be an aqueous solution of potassium hydroxide and / or sodium hydroxide with a mass concentration of 30% to 40%. The pH of the electrolyte can be greater than or equal to 13. High-concentration strong alkaline electrolytes have excellent ionic conductivity, which can reduce the ohmic resistance of the electrolysis process.
[0082] The alkaline electrolyzer may also include a diaphragm that separates the hydrogen produced at the cathode from the oxygen produced at the anode, while allowing hydroxide ions to pass through to conduct charge. Those skilled in the art can select a suitable diaphragm based on actual needs. For example, the diaphragm material can be a porous polymer, ceramic, etc.
[0083] According to another embodiment of this application, the above-mentioned electrocatalytic material is provided for use in alkaline water electrolysis for hydrogen production and alkaline water electrolysis for oxygen production.
[0084] According to the embodiments of this disclosure, applying the above-mentioned electrocatalytic material to alkaline water electrolysis for hydrogen production and alkaline water electrolysis for oxygen production can improve the efficiency and stability of electrolytic catalysis.
[0085] The present application is further illustrated below through embodiments, accompanying drawings, and related test experiments and results. In the following detailed description, numerous specific details are set forth to provide a comprehensive understanding of the embodiments of the present application for ease of explanation. However, it is apparent that one or more embodiments may be implemented without these specific details. Moreover, the details in the following embodiments can be arbitrarily combined to form other feasible embodiments without conflict.
[0086] It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of this application is not limited thereto. The chemicals and raw materials used in the following embodiments are all commercially available or prepared using recognized processing methods.
[0087] Example 1
[0088] This embodiment provides an electrocatalytic material and an electrode including the same, which are prepared by the following method:
[0089] (1) Select a plain weave nickel mesh (nickel metal mesh, or nickel mesh for short) with a size of 20cm×20cm, polish its surface by sandblasting, and then use ethanol and deionized water to ultrasonically clean for 10 minutes. After cleaning, place it in a cool and dry place to air dry naturally to obtain nickel mesh-I.
[0090] (2) Dissolve 0.2 mol sodium metavanadate, 1 mol nickel acetate tetrahydrate and 10 mol urea in 2 L of deionized water to prepare an impregnation solution.
[0091] (3) Heat at a constant temperature of 90°C until solid precipitate begins to appear in the impregnation solution. Use a thick nickel wire to hook the four corners of nickel mesh-I and slowly immerse it horizontally into the obtained saturated solution. After standing for 1 minute, take it out to obtain nickel mesh-II.
[0092] (4) Nickel mesh-II was sent into the calcining furnace and nitrogen was continuously introduced to maintain an inert atmosphere in the furnace. Then the temperature was increased to 550°C at a rate of 20°C / min and kept constant for 2 hours. After that, it was cooled naturally and ultrasonicated for 10 minutes to remove the coating with poor adhesion. It was then cleaned with ethanol and deionized water to obtain nickel mesh-III.
[0093] (5) Electrodeposition was performed using nickel mesh-III as the working electrode, nickel mesh-I (made separately) as the counter electrode, and calomel electrode as the reference electrode. The electrodeposition solution contained 0.2 mol / L nickel sulfate hexahydrate, 0.05 mol / L zinc sulfate hexahydrate, and 15 g / L sodium tetraborate. The pH of the solution was adjusted to 6-7 using boric acid.
[0094] (6) A nickel-zinc catalyst layer was grown on the surface of nickel mesh-III using a dual-current pulse method with a pulse current of -10mA and a pulse count of 1000 times. After electrodeposition, it was immersed in a 10wt% sodium hydroxide solution for 6 hours, then washed with deionized water and placed in a cool, dry place to air dry naturally to obtain nickel mesh-IV as an electrode.
[0095] Example 2
[0096] This embodiment provides an electrocatalytic material and an electrode including the same, which are prepared by the following method:
[0097] (1) Select a plain weave nickel mesh with a size of 20cm×20cm, polish its surface by sandblasting, and then use ethanol and deionized water to ultrasonically clean for 10 minutes. After cleaning, place it in a cool and dry place to air dry naturally to obtain nickel mesh-I.
[0098] (2) Dissolve 1 mol sodium metavanadate, 1 mol nickel acetate tetrahydrate and 40 mol urea in 2 L of deionized water to prepare an impregnation solution.
[0099] (3) Heat at a constant temperature of 80°C until solid precipitate begins to appear in the impregnation solution. Use a thick nickel wire to hook the four corners of nickel mesh-I and slowly immerse it horizontally into the obtained saturated solution. After standing for 1 minute, take it out to obtain nickel mesh-II.
[0100] (4) Nickel mesh-II was sent into the calcining furnace and nitrogen was continuously introduced to maintain an inert atmosphere in the furnace. Then the temperature was increased to 800°C at a rate of 20°C / min and kept constant for 1 hour. After that, it was cooled naturally and ultrasonicated for 10 minutes to remove the coating with poor adhesion. It was then cleaned with ethanol and deionized water to obtain nickel mesh-III.
[0101] (5) Electrodeposition was performed using nickel mesh-III as the working electrode, nickel mesh-I (made separately) as the counter electrode, and calomel electrode as the reference electrode. The electrodeposition solution contained 0.1 mol / L nickel sulfate hexahydrate, 0.03 mol / L zinc sulfate hexahydrate, and 18 g / L sodium tetraborate.
[0102] (6) A nickel-zinc catalyst layer was grown on the surface of nickel mesh-III using a dual-current pulse method. The pulse current was -5mA and the number of pulses was 2000. After electrodeposition, it was immersed in a 10wt% sodium hydroxide solution for 6 hours. After removal, it was washed with deionized water and then placed in a cool and dry place to air dry naturally to obtain nickel mesh-IV as an electrode.
[0103] Example 3
[0104] This embodiment provides an electrocatalytic material and an electrode including the same, which are prepared by the following method:
[0105] (1) Select a plain weave nickel mesh with a size of 20cm×20cm, polish its surface by sandblasting, and then use ethanol and deionized water to ultrasonically clean for 10 minutes. After cleaning, place it in a cool and dry place to air dry naturally to obtain nickel mesh-I.
[0106] (2) Dissolve 3 mol sodium metavanadate, 0.5 mol nickel acetate tetrahydrate and 3 mol urea (600 g) in 2 L of deionized water to prepare an impregnation solution.
[0107] (3) Heat at a constant temperature of 95°C until solid precipitate begins to appear in the impregnation solution. Use a thick nickel wire to hook the four corners of nickel mesh-I and slowly immerse it horizontally into the obtained saturated solution. After standing for 1 minute, take it out to obtain nickel mesh-II.
[0108] (4) Nickel mesh-II was sent into the calcining furnace and nitrogen was continuously introduced to maintain an inert atmosphere in the furnace. Then the temperature was increased to 1000℃ at a rate of 20℃ / min and kept constant for 1 hour. After that, it was cooled naturally and ultrasonicated for 10 minutes to remove the coating with poor adhesion. It was then cleaned with ethanol and deionized water to obtain nickel mesh-III.
[0109] (5) Electrodeposition was performed using nickel mesh-III as the working electrode, nickel mesh-I (made separately) as the counter electrode, and calomel electrode as the reference electrode. The electrodeposition solution contained 0.05 mol / L nickel sulfate hexahydrate, 0.01 mol / L zinc sulfate hexahydrate, and 20 g / L sodium tetraborate.
[0110] (6) A nickel-zinc catalyst layer was grown on the surface of nickel mesh-III using a dual-current pulse method. The pulse current was -20mA and the number of pulses was 200. After electrodeposition, it was immersed in a 10wt% sodium hydroxide solution for 6 hours. After removal, it was washed with deionized water and then placed in a cool and dry place to air dry naturally to obtain nickel mesh-IV as an electrode.
[0111] Example 4
[0112] This embodiment provides an electrocatalytic material and an electrode including the same, referring to Embodiment 3, except that 3 mol of sodium metavanadate is replaced with 0.4 mol of sodium molybdate in the impregnation solution in step (2).
[0113] Comparative Example 1
[0114] This comparative example provides an electrocatalytic material and an electrode including the same, referring to Example 1, except that the nickel mesh-III from Example 1 is used as the electrode.
[0115] Comparative Example 2
[0116] This comparative example provides an electrocatalytic material and an electrode including the same, referring to Example 1, except that sodium metavanadate is not included in the impregnation solution in step (2).
[0117] Comparative Example 3
[0118] This comparative example provides an electrocatalytic material and an electrode including the same, referring to Example 1, except that in step (5), the electrodeposition solution does not include zinc sulfate hexahydrate.
[0119] The electrode (nickel mesh-IV) provided in Example 1 was subjected to the following characterization tests, and the relevant test methods and results are as follows:
[0120] (1) Microscopic testing
[0121] Samples measuring 2cm × 1cm were cut from nickel mesh IV and mounted as metallographic specimens based on the radial section. Local observation of the mounted samples was then performed using a three-dimensional super-depth-of-field digital microscope. The local observation images are shown below. Figure 3 As shown.
[0122] from Figure 3 It is known that the radial cross-section of the nickel wire in the nickel braided mesh (substrate) is approximately elliptical, with two surface layers (a first surface layer and a second surface layer) on its periphery. The inner layer (first surface layer), tightly adhering to the nickel wire, is formed by thermal decomposition, resulting in a rich cavity structure within it; a small amount of vanadium doping deepens its color. The outer layer (second surface layer) is formed by electrodeposition; immersion in sodium hydroxide allows zinc to fully dissolve, forming a distinct porous structure. The "shell-like layer" formed by electrodeposition protects the thermally decomposed inner layer and improves stability.
[0123] Energy-dispersive X-ray spectroscopy elemental analysis was performed on this local area, and the results are as follows: Figure 4 As shown. In this local region, the main metallic element contained in nickel mesh-IV is Ni, with an atomic ratio of up to 95.3%; in contrast, V and Zn elements are dispersed in the inner and outer layers of the material, with atomic ratios of 3.9% and 0.8%, respectively.
[0124] (2) X-ray diffraction test
[0125] Nickel mesh-IV was analyzed using a Bruker X-ray diffractometer, and the results are as follows: Figure 5 As shown.
[0126] from Figure 5 It can be seen that the three main diffraction peaks can all be attributed to the characteristic peaks of Ni. This shows that the inert gas protection and electrochemical deposition effectively prevented the oxidation of the active components. The electrode composition is still mainly Ni elemental, and the alkaline immersion activation process can effectively remove the zinc deposit on its surface.
[0127] It is understandable that the nickel oxide and nickel hydroxide formed on the surface of the nickel mesh-IV are only nanometers thick, which is relatively small compared to the tens of micrometers of elemental nickel in the inner layer, and therefore not detected by X-ray diffraction.
[0128] (3) X-ray photoelectron spectroscopy of nickel
[0129] The nickel mesh-IV was analyzed using X-ray photoelectron spectroscopy, and the results are as follows: Figure 6 As shown. From Figure 6 It can be seen that metallic nickel in the material has three binding energies: 852, 853, and 855 eV, which correspond to Ni, respectively. 0 NiO and Ni(OH)2. Since XPS can only detect metallic nickel at a depth of less than 10 nm, while the coating thickness can exceed 5 μm, the material is mainly composed of elemental nickel in the outer layer.
[0130] It is understandable that different elements will have different positions in XPS spectra; vanadium and zinc mainly appear in the ranges of 500–520 eV and 1015–1025 eV, respectively. This test only focuses on nickel in the nickel mesh-IV, and there is no need to analyze trace elements.
[0131] Application Example 1
[0132] The electrode assembly provided in Example 1, with the cathode as the cathode and the nickel braided mesh as the anode, was subjected to an electrolysis at 4000 A / m using an alkaline electrolytic cell under normal pressure. 2 The device underwent 150 hours of continuous testing, with sample sizes of 5cm × 5cm. It was assembled using a composite diaphragm and EPDM gaskets, with a 30wt% KOH solution as the electrolyte, an alkaline solution flow rate of 30mL / min, and an oxygen-side bath temperature of 85±1℃.
[0133] Application Example 2
[0134] The alkaline electrolytic cell provided in this application example is the same as that in application example 1, except that the cathode is the electrode provided in example 1, and the anode is also the electrode provided in example 1.
[0135] Application Example 3
[0136] The alkaline electrolytic cell provided in this application example is the same as that in application example 1, except that the cathode is the electrode provided in example 4.
[0137] Compare and contrast examples 1-3
[0138] The alkaline electrolytic cells provided in Comparative Examples 1 to 3 are the same as those in Comparative Example 1, except that the cathodes are the electrodes provided in Comparative Examples 1 to 3 respectively.
[0139] The test results for Application Examples 1-3 and Comparative Application Examples 1-3 are shown in Table 1 and 2. Figure 8 From Table 1 and Figure 8 It can be seen that in the combination of nickel mesh-IV as the cathode and nickel braided mesh as the anode (Application Example 1), the cell voltage tends to stabilize (1.823V) after 40 hours of testing, and the voltage is 1.828V after 150 hours of operation. Under the same conditions, if nickel mesh-IV is used as both the cathode and anode (Application Example 2), the energy consumption can be further reduced, and the voltage is only 1.811V after 150 hours of operation.
[0140] In contrast, if sodium metavanadate in the raw materials for preparing the impregnation solution in the second step is replaced with sodium molybdate, the sample prepared by this method (Application Example 3) has slightly worse performance. The voltage is 1.829V when the running time reaches 40h, and it will reach 1.842V at 150h. The increase (13mV) is greater than that of Application Example 1 (5mV) and Application Example 2 (-4mV).
[0141] Furthermore, compared with the three cathode materials corresponding to Application Examples 1-3, their initial performance and voltage increase during operation are significantly worse than those of Application Examples 1-3.
[0142] Table 1
[0143]
[0144] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this application. It should be understood that the above descriptions are merely specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. An electrocatalytic material, comprising a first surface layer and a second surface layer sequentially disposed on the surface of a substrate, wherein, The first surface layer comprises a composite containing at least one element selected from molybdenum and vanadium and an element nickel, the second surface layer comprises metallic nickel, and the second surface layer has a porous structure.
2. The electrocatalytic material according to claim 1, wherein, The complex containing at least one element from molybdenum and vanadium and nickel includes a complex containing vanadium and nickel.
3. The electrocatalytic material according to claim 1, wherein, The thickness of the first surface layer is 15-30 micrometers; The thickness of the second surface layer is 10 to 50 micrometers.
4. The electrocatalytic material according to claim 1, wherein, The first surface layer has a porous structure.
5. The electrocatalytic material according to claim 1, wherein, In the electrocatalytic material, the mass content of nickel is 90%~98%, and the mass content of molybdenum and / or vanadium is 2%~10%.
6. The electrocatalytic material according to claim 1, wherein, The second surface layer also includes an amphoteric metal, wherein the mass content of the amphoteric metal is less than or equal to 5%.
7. The electrocatalytic material according to claim 1, wherein, In the first surface layer, the composite containing at least one of molybdenum, vanadium, and nickel includes at least one of vanadium oxide, vanadium hydroxide, molybdenum oxide, molybdenum hydroxide, nickel oxide, and nickel hydroxide.
8. The electrocatalytic material according to any one of claims 1 to 7, wherein, The second surface layer further comprises at least one of nickel oxide and nickel hydroxide.
9. The electrocatalytic material according to any one of claims 1 to 7, wherein, The material of the substrate includes at least one of nickel and nickel alloys; The substrate includes at least one of metal mesh and metal foam.
10. The electrocatalytic material according to any one of claims 1 to 7, wherein, The substrate is a surface-treated substrate; The surface treatment includes at least one of sandblasting, grinding, chemical etching, and electrochemical etching.
11. A method for preparing an electrocatalytic material, comprising: A first initial surface layer is prepared on the surface of a substrate to obtain a first initial surface layer located on the surface of the substrate. A composite film is electrodeposited on the surface of the first initial surface layer away from the substrate, and the first initial surface layer is transformed into a first surface layer to obtain a first surface layer and a composite film located on the surface of the substrate. The composite film includes metallic nickel and an amphoteric metal, and the first surface layer includes a composite containing at least one element selected from molybdenum and vanadium and nickel. The amphoteric metal in the composite film is removed by alkaline washing, thereby transforming the composite film into the second surface layer and obtaining the electrocatalytic material.
12. The method for preparing the electrocatalytic material according to claim 11, wherein, The complex containing at least one element from molybdenum and vanadium and nickel includes a complex containing vanadium and nickel.
13. The method for preparing the electrocatalytic material according to claim 11 or 12, wherein, The step of preparing a first initial surface layer on the substrate surface to obtain a first initial surface layer located on the substrate surface includes: The substrate is impregnated in an impregnation solution to obtain an impregnated substrate, wherein the impregnation solution includes nickel salt, molybdate and / or metavanadate, and a precipitant; The impregnated substrate is calcined under a protective atmosphere to obtain the first initial surface layer located on the surface of the substrate.
14. The method for preparing the electrocatalytic material according to claim 13, wherein, The nickel salt includes at least one of nickel acetate and nickel nitrate; The molybdate includes at least one of sodium molybdate and ammonium molybdate; The metavanadate includes at least one of sodium metavanadate and ammonium metavanadate. The precipitant includes at least one of urea and melamine; In the impregnation solution, the molar ratio of the nickel salt, the molybdate and / or metavanadate, and the precipitant is (1~5):(1~5):(1~50).
15. The method for preparing the electrocatalytic material according to claim 13, wherein, The process of impregnating the substrate in the impregnation solution includes: immersing the substrate in the impregnation solution at 70~100°C for 1~10 minutes; The calcination temperature is 500~1000℃; the calcination time is 1~5 hours.
16. The method for preparing the electrocatalytic material according to claim 11 or 12, wherein, The amphoteric metal includes at least one of zinc, chromium, and aluminum; The electrodeposition solution used for electrodeposition includes nickel salt, amphoteric metal salt, and pH buffer. In the electrodeposition solution, the nickel salt includes at least one of nickel sulfate, nickel acetate, and nickel nitrate; the amphoteric metal salt includes at least one of zinc sulfate, zinc acetate, zinc nitrate, chromium sulfate, chromium nitrate, aluminum nitrate, and aluminum sulfate; and the pH buffer includes at least one of boric acid, sodium borate, and phosphoric acid. In the electrodeposition solution, the concentration of the nickel salt is 0.05~0.2 mol / L, the concentration of the amphoteric metal salt is 0.01~0.05 mol / L, and the concentration of the pH buffer is 15~20 g / L; The electrodeposition includes: placing the first initial surface layer located on the substrate surface in an electrodeposition solution and repeating the following pulses 200 to 2000 times: current -5 to -20 mA, time 5 to 30 s, current 0 mA, time 5 to 15 s.
17. The method for preparing the electrocatalytic material according to claim 11 or 12, wherein, The alkaline washing includes: immersing the first surface layer and the composite film located on the substrate surface in an alkaline solution, and then drying them to obtain the electrocatalytic material; The alkaline solution includes at least one of sodium hydroxide and potassium hydroxide.
18. An electrode comprising a substrate and an electrocatalytic material located on the surface of the substrate, wherein the electrocatalytic material is the electrocatalytic material according to any one of claims 1 to 10 or the electrocatalytic material prepared by any one of claims 11 to 17.
19. The application of an electrocatalytic material according to any one of claims 1 to 10 or an electrocatalytic material prepared by any one of claims 11 to 17 in alkaline water electrolysis for hydrogen production and alkaline water electrolysis for oxygen production.